2013
DOI: 10.1111/gcb.12290
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions in the Shanghai river network: implications for the effects of urban sewage and IPCC methodology

Abstract: Global nitrogen (N) enrichment has resulted in increased nitrous oxide (N(2)O) emission that greatly contributes to climate change and stratospheric ozone destruction, but little is known about the N(2)O emissions from urban river networks receiving anthropogenic N inputs. We examined N(2)O saturation and emission in the Shanghai city river network, covering 6300 km(2), over 27 months. The overall mean saturation and emission from 87 locations was 770% and 1.91 mg N(2)O-N m(-2) d(-1), respectively. Nitrous oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 31 publications
9
76
0
Order By: Relevance
“…Very high levels of pCO 2 observed in the lower reach of the Han River (up to 4132 atm) and its three 290 urban tributaries (up to 11970 atm) fall in the high ranges found in some polluted rivers in Europe (Kempe, 1984;Frankignoulle et al, 1998;Borges et al, 2006) and China (Yao et al, 2007;Ran et al, 2015;Liu et al, 2016;. Consistent with these previous reports on pCO 2 and other studies reporting high levels of CH 4 and N 2 O in polluted urban waters (Garnier et al, 2013;Yu et al, 2013;Smith et al, 2017;Wang et al, 2017bWang et al, , 2018, the results observed in this study emphasize the dominant influence of urban tributaries carrying wastewater as a primary anthropogenic source of GHGs 295 in the highly urbanized river system. Different longitudinal patterns in three GHGs (Fig.…”
Section: Reach-specific Patterns and Controls On Three Ghgssupporting
confidence: 79%
See 2 more Smart Citations
“…Very high levels of pCO 2 observed in the lower reach of the Han River (up to 4132 atm) and its three 290 urban tributaries (up to 11970 atm) fall in the high ranges found in some polluted rivers in Europe (Kempe, 1984;Frankignoulle et al, 1998;Borges et al, 2006) and China (Yao et al, 2007;Ran et al, 2015;Liu et al, 2016;. Consistent with these previous reports on pCO 2 and other studies reporting high levels of CH 4 and N 2 O in polluted urban waters (Garnier et al, 2013;Yu et al, 2013;Smith et al, 2017;Wang et al, 2017bWang et al, , 2018, the results observed in this study emphasize the dominant influence of urban tributaries carrying wastewater as a primary anthropogenic source of GHGs 295 in the highly urbanized river system. Different longitudinal patterns in three GHGs (Fig.…”
Section: Reach-specific Patterns and Controls On Three Ghgssupporting
confidence: 79%
“…Direct influences of wastewater-derived GHGs have been observed in urban rivers receiving WWTP effluents (Garnier et al, 2013;Yu et al, 2013;Burgos et al, 2015;Alshboul et al, 2016;Wang et al, 2017a;Yoon et al, 2017). For example, large pulses of CH 4 and N 2 O in the Guadalete River estuary in Spain were found 350 near the discharge from a WWTP, as a combined result of direct gas emissions from WWTP effluents and indirect effects on the production of CH 4 and N 2 O in water channel and benthic sediments downstream (Burgos et al, 2015).…”
Section: Spatial Variations In Three Ghgs Observed Along the Middle Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Agriculture (livestock and rice cultivation) contributes globally to about 57% of total anthropogenic CH 4 emissions (Saunois et al, 2016). Here, we show that rivers can be an additional source of CH 4 related to agricultural practise (croplands and pastures) that has not been previously accounted, although already acknowledged for N 2 O (Yu et al, 2013). Unlike impounded rivers such as the Mississippi where low CO 2 values have been reported due to planktonic primary production , the Meuse was characterized by CO 2 oversaturation that increased in summer.…”
Section: Discussionmentioning
confidence: 63%
“…Organic matter inputs from wastewater enhance organic matter degradation and the production of CO 2 and CH 4 (Abril et al, 2000;Garnier et al, 2013;Marwick et al, 2014); effluents from wastewater treatment plants are enriched in CO 2 and CH 4 that are degassed within the river network (Alshboul et al, 2016). In extreme cases of wastewater pollution, anoxic conditions will lead to low N 2 O levels due to denitrification (Rajkumar et al, 2008), but in oxic conditions nitrification fuelled by NH 4 + inputs from wastewater leads to N 2 O production (Garnier et al, 2009;Yu et al, 2013;Marwick et al, 2014). Impoundments increase water residence time that favour organic matter sedimentation and CH 4 production (Maeck et al, 2013;Crawford et al, 2016).…”
Section: Introductionmentioning
confidence: 99%